Evaluation of the mechanical properties of SS-316L thin foils by small punch testing and finite element analysis. (15th October 2015) - Haroush, S.; Priel, E.; Moreno, D.; Busiba, A.; Silverman, I.; Turgeman, A.; Shneck, R.; Gelbstein, Y.
Graphical abstract: Highlights: Classical yield stress estimation from SPT fails for specimens thinner than 300 μm. A verified and validated FE model of SPT for non-standard specimens is presented. A "transition zone" between plate bending and membrane stretching is defined. A relation for estimation of the yield stress in the "transition zone" is proposed. Abstract: Thin foils having thickness values of 200 μm and less are commonly applied in the food industries, medical applications and more. Small punch technique (SPT) is a promising mechanical testing method for specimens thicker than 250 μm, in which a formulation correlating the measured parameters to standard tensile properties was previously reported. The current research is focused, for the first time, on the correlation between SPT and tensile mechanical properties of SS-316L thinner specimens in the range of 100–200 μm. It is demonstrated by finite-element-analysis, that the mechanical response of thin foils having thicknesses in the range of 25–500 μm can be divided into three categories. For specimens thicker than 300 μm, thin plate bending equations that were applied previously for thick specimens, are still valid, while for thinner specimens this theory fails to provide adequate correlation between SPT and tensile yield stress. For specimens thinner than 50 μm it was identified that equations derived from membrane solution should be employed rather than classical plate theory. For intermediate thickness values in the 50–300 μm range, a "transition-zone" was identified between plate and membrane-like mechanical responses. For the lower region, 50–100 μm, an analytical expression correlating the measured SPT parameters and the tensile yield stress is currently proposed.